Enhancing thermal and ionic conductivities of electrospun PAN and PMMA nanofibers by graphene nanoflake additions for battery‐separator applications. (18th April 2014) - Khan, W. S.; Asmatulu, R.; Rodriguez, V.; Ceylan, M.
SUMMARY The present study reports the fabrication and characterization of electrospun polyacrylonitrile (PAN) and polymethyl methacrylate (PMMA) nanofiber separators embedded with graphene nanoflakes. Different weight percentages (0, 2, 4, and 8 wt%) of graphene nanoflakes were dispersed in dimethylformamide (DMF) and ethanol using sonication and high‐speed agitations, and then PAN and PMMA powders were added to the dispersions prior to the mixing process. Ratios of 85:15 for DMF : PAN and 88:12 for ethanol : PMMA were chosen during the dispersion and dissolution processes. After the fabrication of the membranes via the electrospinning process, thermal, dielectric, ionic, and surface hydrophobic properties of the PAN and PMMA nanofiber separators were investigated in detail. Test results revealed that the physical properties, such as wettability, dielectric constant, ionic conductivity, and thermal conductivity values of the nanocomposite separators were significantly increased as a function of graphene concentrations. For example, the water contact angle, ionic conductivity, dielectric constant, and thermal conductivity values of the membranes were increased from 120° to 145°, 3.31 × 10−4 to 5.52 × 10−4 S/m, 3.5 to 8.5 W/m K, and 1.0 to 5.0 W/m K, respectively, when the graphene concentration was increased from 0% to 8% in PMMA. Similar trends were observed in the PAN fibers, as well. Lithium‐ion (Li‐ion) batteries have become the major source of power for portable electronic devices, and because separators are one of the major components of these batteries, the present alternatives can be an option for long‐lasting Li‐ion battery fabrications. Copyright © 2014 John Wiley & Sons, Ltd.